2010
DOI: 10.1097/paf.0b013e3181c6bed9
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death From Massive Gastrointestinal Hemorrhage Associated With Crack Cocaine Use

Abstract: Cocaine is associated with many health complications including gastrointestinal ischemia/infarction, and hemorrhage. The clinical medical literature describes such entities, but no case exists within the forensic literature describing life-threatening intraluminal gastrointestinal hemorrhage and sudden death associated with cocaine. A 48-year-old black man died suddenly in his home, with drug paraphernalia near the body. Further investigation revealed blood stains on upholstery, and a toilet filled with fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Ischaemic‐pattern colitis has been reported in association with a variety of drugs, including oral contraceptives, ergotamine derivatives, cocaine and, potentially, sumatriptan [a serotonin‐1 5‐hydroxytryptamine (5‐HT 1) receptor agonist] overuse . Rare cases of ischaemic colitis associated with interferon‐alpha (IFN‐α) treatment for chronic hepatitis C (HCV) infection and metastatic cancer have been reported .…”
Section: Ischaemic‐pattern Colitismentioning
confidence: 99%
“…Ischaemic‐pattern colitis has been reported in association with a variety of drugs, including oral contraceptives, ergotamine derivatives, cocaine and, potentially, sumatriptan [a serotonin‐1 5‐hydroxytryptamine (5‐HT 1) receptor agonist] overuse . Rare cases of ischaemic colitis associated with interferon‐alpha (IFN‐α) treatment for chronic hepatitis C (HCV) infection and metastatic cancer have been reported .…”
Section: Ischaemic‐pattern Colitismentioning
confidence: 99%
“…Similar report of cocaine associated GIT bleeding have been documented in past (23,24). It is suggested that massive GIT bleeding could contribute to high mortality rate seen in drug packers with ruptured contents (25,26) A wide range of pathological effects were seen in CNS during autopsy that ranged from intracerebral haemorrhages to ischaemic changes (encaphalomalacia). This is in agreement with the findings of Schreiber et al, (11).…”
Section: Discussionmentioning
confidence: 53%
“…Other complications that have been described include subarachnoid hemorrhage, obstetric complications, sexual dysfunction, and a variety of psychiatric disorders. [7] Rapid diagnosis of pneumomediastinum is important because it is a potentially lethal condition. Serious complications such as tension and bilateral pneumothorax as well as tension pneumomediastinum, which causes cardiac compression and reduces cardiac output, have also been reported.…”
Section: Discussionmentioning
confidence: 99%